2009
DOI: 10.25200/bjr.v5n2.2009.214
|View full text |Cite
|
Sign up to set email alerts
|

Pushed news: when the news comes to the cellphone

Abstract: Combining two findings of recent surveys on the Internet which state that 1) "the Internet will soon surpass all other media as a main source for national and international news" and 2) "the mobile device will be the primary connection tool to the Internet in 2020" leads us to the conclusion that smartphones will soon be the primary source for news access. But if so, how will news come to the Internetconnected cellphones? In accordance with the distinction, already drawn in 1997, between push and pull technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…Research focussing on mobile notifications is scarce and has only partly studied push notifications as one of mobile journalism's many components (see L opez-Garc ıa et al 2019). Fidalgo (2009) mapped the Portuguese news media alerts service and found that personalisation of notification services resided within the paid options at a time when SMS was the predominant option. Fidalgo contends that due to the personalised mass communication nature of mobile phones, news organisations should be aware that "the amount, the kind and the frequency of the news individuals want to receive through push technology is totally dependent upon them" (2009,120).…”
Section: The Flow Of News Consumption? Time Personalisation and Audmentioning
confidence: 99%
See 1 more Smart Citation
“…Research focussing on mobile notifications is scarce and has only partly studied push notifications as one of mobile journalism's many components (see L opez-Garc ıa et al 2019). Fidalgo (2009) mapped the Portuguese news media alerts service and found that personalisation of notification services resided within the paid options at a time when SMS was the predominant option. Fidalgo contends that due to the personalised mass communication nature of mobile phones, news organisations should be aware that "the amount, the kind and the frequency of the news individuals want to receive through push technology is totally dependent upon them" (2009,120).…”
Section: The Flow Of News Consumption? Time Personalisation and Audmentioning
confidence: 99%
“…For example, Xu et al found that "the adoption of a mobile news app significantly increases the probability of visiting the provider's corresponding mobile website" (2014,109). This is also true for push notification alerts which is selected and directly "pushed" into users' mobile phones (Fidalgo 2009).…”
mentioning
confidence: 99%
“…Essas aplicações oferecem aos utilizadores serviços de push news ou recebimento de alertas noticiosas por meio de notificações enviadas sem o requerimento imediato do usuário. Fidalgo (2009) enfatiza que a tecnologia push é uma das principais características que distingue a oferta de notícias no telefone celular de outros meios, uma vez que o smartphone está ligado 24 horas por dia e ao longo desse período pode receber informações através de um recurso nativo inserido em rotinas de sistemas operacionais, tais como iOS e Android. No browser as notificações são mais restritas, limitando-se ao próprio navegador.…”
Section: Introductionunclassified
“…Para Silveira, as affordances "é a potência, é uma pré-condição do sistema/ objeto para a atividade", ou seja, a sua existência "não obriga que a ação que ela pressupõe seja efetuada, mas a potência dela ocorrer está ali" (2019, p. 64). Fidalgo (2009) lembra que a construção e difusão da notícia para os dispositivos móveis é possível a partir de um trabalho em equipe que conjuga diversas habilidades. Além de jornalistas, a atuação de programadores e designers é essencial.…”
Section: Introductionunclassified
“…Users no longer needed to search for information and wait for long durations of time as it loads; they could simply have the information they are interested in delivered to their mailbox (Lasica, 1997. ) In fact, people found the concept of a "push" so appealing that several news providers offered paid subscription services for breaking news SMS alerts (Fidalgo, 2009). Since then, much has changed.…”
Section: Introductionmentioning
confidence: 99%